2020
DOI: 10.1007/s13629-020-00296-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical impact of PSMA PET in biochemically recurrent prostate cancer; a review of the literature

Abstract: PSMA PET is increasingly used for localising biochemical recurrent prostate cancer (BCR) and is incorporated in European and national guidelines. Nevertheless, clinical implications of PSMA PET need to be clarified. In this report, the available literature on the clinical impact of PSMA PET in patients with BCR is reviewed. A comprehensive literature search was performed using the MEDLINE® database. All studies reporting data on PSMA PET directed patient management were considered relevant. In the review, 16 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Positron emission tomography (PET), combined with either computer tomography (CT) or magnetic resonance imaging (MRI), utilizing radiotracers that bind to prostate-specific membrane antigen (PSMA) is an excellent diagnostic tool for prostate cancer imaging. In the past few years, PSMA-PET has evolved to become the leading advanced imaging modality, especially for patients with early biochemical recurrence (BCR) [1,2]. In various studies, PSMA-PET/CT has shown better detection efficacy in early BCR than MRI, CT, conventional imaging [3][4][5][6], or choline-labeled PET ligands [7], and showed substantial impact on management [8].…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET), combined with either computer tomography (CT) or magnetic resonance imaging (MRI), utilizing radiotracers that bind to prostate-specific membrane antigen (PSMA) is an excellent diagnostic tool for prostate cancer imaging. In the past few years, PSMA-PET has evolved to become the leading advanced imaging modality, especially for patients with early biochemical recurrence (BCR) [1,2]. In various studies, PSMA-PET/CT has shown better detection efficacy in early BCR than MRI, CT, conventional imaging [3][4][5][6], or choline-labeled PET ligands [7], and showed substantial impact on management [8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies use this fact to investigate possible PSMA-guided surgery in these patients ( 25 ). A very recent review revealed PSMA-PET/CT as an indicator for metastasis targeted therapies in patients with recurrent PCa ( 26 ). So, it is most important to exactly detect and locate lymph node metastases before salvage treatment of PCa, as well as in recurrent PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in techniques of imaging to locate sites of recurrence and to guide biopsies or focal therapies have been considerable. PSMA-PET imaging and dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) are useful tools for defining regions suspicious for recurrence [ 5 , 18 21 ]. Furthermore, considerable advances in precise treatment planning and delivery, as well as the introduction of endo-rectal balloons (ERBs) [ 22 , 23 ] and spacers [ 24 26 ] have improved the ability to offer safer re-irradiation in recurrent disease.…”
Section: Introductionmentioning
confidence: 99%